CO2-free conversion of fossil fuels by multiphase plasma at ambient conditions. (15th November 2021) - Wang, Kunpeng; Baky, Abdullah Hill; Bhuiyan, Shariful Islam; Kraus, Jamie; Campbell, Christopher; Stanich, Rollie; Jemison, Howard; Staack, David
Highlights: About 13% conversion was achieved with 500 kJ/kg energy input. Large alkane molecules converted to intermediate alkane and alkene molecules and aromatics. Heavy oil and methane co-converted to fuel products and hydrogen. Chemical conversion occurred at ambient conditions with Zero GHG emissions. Electrical pulsing energy controls conversion and product selectivity. Abstract: Heavy oil conversion to fuel products and petrochemicals are both energy and greenhouse gas (GHG) emission intensive. Chemical reactions must be activated by high temperature and pressure or both with specific catalysts. Catalysts require constant regeneration by burning off coke which emits tremendous GHGs. Scale of reaction system is usually massive to maintain high energy efficiency. Here, we show an electrical method that uses nanosecond pulsed plasma to convert liquid fuels at ambient conditions with minimized GHG emissions. Plasma was generated on the interface of natural gas bubbles and liquid fuels (hexadecane). Interaction with plasma is able to convert both into valuable products including hydrogen and intermediates. Pulsing energy was the key to liquid conversion and product selectivity. Using lower pulsing energy (20 mJ), this process converts 13% of liquid fuel and 5% of methane primarily to hydrogen and C2 H2 and to intermediate products (7%) and branched alkane products (3%). Energy cost was less than 1% of the energy content of processed fuel. Higher pulsing energy (200 mJ) primarily converts liquid fuels to solid products. This method is electrical, flexible on scale and easily integrated with renewable electricity.